ELEMEN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING PADA SISWA KELAS IV SD - SUGIANTI, NI KADEK; HUSAIN, RUSMIN; PULUKADANG, WIWY T.; MONOARFA, FIDYAWATI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study aims to improve the reading comprehension skills of fourth grade students of SD Negeri 2 Kabila through the application of the Snowball Throwing learning model. This study uses a quantitative approach with the classroom action research (CAR) method. The subjects of this study were 20 fourth grade students. Data on students' reading comprehension skills were collected through tests and analyzed quantitatively descriptively. The results of the study showed a significant increase in students' reading comprehension skills from cycle I to cycle II. In cycle I, 13 students (65%) achieved the set performance indicators, but had not met the 75% success criteria. In cycle II, there was an increase to 20 students (100%) who achieved the performance indicators, exceeding the set success target. This study concludes that the Snowball Throwing learning model is effective in improving the reading comprehension skills of fourth grade students of SD Negeri 2 Kabila. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan membaca pemahaman siswa kelas IV SD Negeri 2 Kabila melalui penerapan model pembelajaran Snowball Throwing. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian tindakan kelas (PTK). Subjek penelitian ini adalah 20 siswa kelas IV. Data kemampuan membaca pemahaman siswa dikumpulkan melalui tes dan dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan peningkatan yang signifikan pada kemampuan membaca pemahaman siswa dari siklus I ke siklus II. Pada siklus I, 13 siswa (65%) mencapai indikator kinerja yang ditetapkan, namun belum memenuhi kriteria keberhasilan 75%. Pada siklus II, terjadi peningkatan menjadi 20 siswa (100%) yang mencapai indikator kinerja, melampaui target keberhasilan yang ditetapkan. Penelitian ini menyimpulkan bahwa model pembelajaran Snowball Throwing efektif dalam meningkatkan kemampuan membaca pemahaman siswa kelas IV SD Negeri 2 Kabila.